2003
DOI: 10.1016/s1201-9712(03)90106-8
|View full text |Cite
|
Sign up to set email alerts
|

How reliable is the history of chickenpox? Varicella serology among children up to 14 years of age

Abstract: A large proportion of the study group (61%), mainly below 7 years of age, is susceptible to varicella. The positive predictive value of a history of varicella is 87.8%, whereas the negative predictive value of a negative history is 11.4%, which means that there is an 88.6% probability of a negative history being correct. Varicella serology may be reasonable prior to vaccination in children >10 years old with a negative chickenpox history. However, if one excludes cost considerations, it is also reasonable to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…Classification bias is unlikely, as true subclinical varicella is rare and clinical diagnosis easy in children presenting lesions [20]. Recall bias should also be limited, given the large positive predictive and negative predictive values of varicella history for school-aged children (95 % and 90 %, respectively) [21][22][23]. Furthermore, our estimates of cumulative incidence of varicella at age 11 years are similar to that of a recent independent French seroprevalence study (90 % at age 11 years [24]) as well as earlier figures in France [25].…”
Section: Discussionmentioning
confidence: 99%
“…Classification bias is unlikely, as true subclinical varicella is rare and clinical diagnosis easy in children presenting lesions [20]. Recall bias should also be limited, given the large positive predictive and negative predictive values of varicella history for school-aged children (95 % and 90 %, respectively) [21][22][23]. Furthermore, our estimates of cumulative incidence of varicella at age 11 years are similar to that of a recent independent French seroprevalence study (90 % at age 11 years [24]) as well as earlier figures in France [25].…”
Section: Discussionmentioning
confidence: 99%
“…Very few studies on the reliability of information on children's varicella history are available [15][16][17][18][19] . The majority of the published investigations was carried out to assess the positive and negative predictive value of the information on varicella history and include children older than seven, adolescents and adults.…”
Section: Discussionmentioning
confidence: 99%
“…The vaccine is recommended for children over one year of age and for adults with negative or doubtful varicella history without a prior serologic test 2 . Although a few studies have assessed the positive and negative predictive value of the information on the varicella antecedents in children and adults [13][14][15][16][17][18][19] , no study was found in the literature assessing the reliability of the information provided by parents of children attending Government day-care centers in the State of São Paulo. Thus, it was decided to conduct this study, because such information is critical in order to establish appropriate public policies to develop vaccination guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Prior chicken pox will be defined by parental report alone because this has been shown to be specific for the diagnosis, and because a physician diagnosis often is not made as children with a suspected diagnosis are discouraged from coming to clinic (to prevent spread to other children). 40 …”
Section: Methodsmentioning
confidence: 99%